Status of Market Reforms in India - Reddy, A Amarender (Indian Farming, 2018)
There was a good improvement in the functioning of the agricultural markets in India with the adoption of Model APMC Act (2003) by many states. There was visible signs of increasing farmers share in consumer’s rupee across many states and many crops. The innovating marketing models like direct marketing by farmers (Rythu bazaars) and contract farming and emandi needs to be encouraged.